The indispensability of mathematics - Colyvan, Mark (Oxford University Press paperback., 2001)
The Quine-Putnam indispensability argument in the philosophy of mathematics urges us to place mathematical entities on the same ontological footing as other theoretical entities indispenable to certain scientific theories. This text examines the issues.